Progressive facial hemiatrophy (Parry-Romberg syndrome): short case report - Puidupin Alexandre; Desoutter Aline; Deneuve Sophie; Nokovitch Lara; Chaux-Bodar (EDP Sciences, 2019)
Introduction: The Parry Romberg syndrome (PRS) is a mosaic disease of unknown aetiology which mostly affects women. The facial hemiatrophy generally begins during the early childhood. It has a great impact on social life, and aesthetic rehabilitation is a major challenge. Observation: A 38 years-old-female patient presented with an enucleation of the left eye, due to multiple hamartomas and progressive facial hemiatrophy. The placement of 2 extraoral implants was proposed to bear an ocular epithesis. Comments: PRS develops between the 2nd and 20th year of life, and stabilizes at the adult age. Its main characteristic is a progressive facial hemiatrophy, which involves skin, fat tissues, muscles and osteocartilaginous tissues. 20% of patients have neurological symptoms, and epilepsy is often described as a side effect of the disease. Conclusion: Diagnosis of localized scleroderma has to be eliminated, as these 2 entities are very similar. Major facial reconstructive surgery is often proposed to restore aesthetics.